Implementation Of Food Security Policy In A Network Governance Perspective: Study At The West Papua Food Security Service - Runi Arrang; Sutrisno Sutrisno; Sigit Wahyudi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Through the Governance Network, the government has a great possibility to reach problems more closely by utilizing the advantages of the network and developing innovative ideas to overcome public problems and improve the quality of services and public policies. One of the problems is the food security policy. This study uses the concept of Social Network Theory (Klijn & Koppenjan) which looks at the structure in the policy implementation network, namely the aspects of contact, trust, information sharing, and resource exchange as well as how to coordinate between actors in the food security policy implementation network in West Papua Province. The results of the study show that the relationship and participation of actors in the network have not run optimally. This can be seen from the structure in the network which includes trust, information sharing, and resource exchange has not been optimal. Meanwhile, contact from the structure in the network has been carried out well, with the formation of policy tools. Coordination in the food security policy implementation network uses the type of mutual adjustment coordination. The implementation of the Food Security Policy in the Perspective of the Governance Network has not been effective.